Postoperative bleeding in paediatric ENT surgery - Bidlingmaier, C.; Olivieri, M.; Stelter, K.; Eberl, W.; von Kries, R.; Kurnik, K. (Hämostaseologie, 2010)
Bleeding after ear-nose-and throat surgery in children is a serious complication. With the help of the German Surveillance Unit for Rare Paediatric Disorders (Erhebungseinheit für seltene pädiatrische Erkrankungen in Deutschland; ESPED) a two year survey was performed to record the incidence, severity, reasons and treatment of haemorrhages. During the study period, 1069 bleeds were reported from 720 paediatric hospitals and departments of otorhinolaryngology after adenoidectomy and tonsillectomy. 713 reports could be analyzed. Two deaths occurred after adenoidectomy. Although laboratory screening was performed in more than 70% of all cases, bleeding complications were neither foreseeable nor preventable. Inherited coagulopathies were rare and in most cases not detected, neither by laboratory screening nor by taking a history. Since preoperative measures cannot help much to improve the situation, all efforts have to be taken to improve the postoperative period, especially since more than 20% of the hemorrhages occurred during weekends. Guidelines on postoperative care and behaviour should therefore be implemented and parents and patients must be informed on bleeding risks and on what to do in case of emergency. If bleeding occurs, extensive coagulation testing is mandatory.
Keywords: Operationen; Kinder; präoperative Diagnostik; postoperative Blutungen